The Roman Inquisition: centre versus peripheries - Aron-Beller, Katherine; Black, Christopher F. (Catholic Christendom, 1300-1700, 2018)
Preliminary Material -- Introduction /Katherine Aron-Beller and Christopher Black -- 1 Conflict and Collaboration /Irene Fosi -- 2 From Madrid to Rome /Kimberly Lynn -- 3 Relations between Inquisitors in Modena and the Roman Congregation in the Seventeenth Century /Christopher Black -- 4 Centre and Periphery /Giuliana Ancona and Dario Visintin -- 5 Interconnected Inquisitors /Jonathan Seitz -- 6 The Holy Office in the Marche of Ancona /Vincenzo Lavenia -- 7 The Roman Inquisition at Novara in the Century of Enlightenment /Thomas Deutscher -- 8 Ripped Shoes and Books of Magic /Federico Barbierato -- 9 “Tacitly denied” /Giorgio Caravale -- 10 Interrogating Conversion /Giorgos Plakotos -- 11 Converting the Jews /Matteo Al Kalak -- 12 The Jewish Inquisitorial Experience in Seventeenth-Century Modena /Katherine Aron-Beller -- 13 Gendered Investigations in Roman Inquisition Tribunals /Gretchen Starr-LeBeau -- 14 Unintentional Dissent /Stefano Villani -- Name Index /Katherine Aron-Beller and Christopher Black -- Subject Index /Katherine Aron-Beller and Christopher Black.